(untitled) (Journal of Artificial Intelligence & Research, 2021)
Artificial intelligence (AI)-driven decision support systems have revolutionized the field of precision medicine by providing clinicians with tools to personalize patient care. These systems leverage machine learning algorithms to analyze complex data sets, including genomics, imaging, and clinical data, to generate actionable insights. This paper examines the development and implementation of AI-driven decision support systems in precision medicine, highlighting their significance in clinical decision-making. We discuss key advancements in AI technologies, challenges in data integration and interpretation, and the impact of AI on improving patient outcomes. Additionally, we explore ethical considerations and future directions for AI-driven decision support systems in precision medicine.